Clinical Holistic Medicine: How to Recover Memory Without “Implanting” Memories in Your Patient - Søren Ventegodt; Isack Kandel; Joav Merrick (The Scientific World Journal)
Every therapeutic strategy and system teach us the philosophy of the treatment system to the patient, but often this teaching is subliminal and the philosophical impact must be seen as “implanted philosophy”, which gives distorted interpretations of past events called “implanted memories”. Based on the understanding of the connection between “implanted memory” and “implanted philosophy” we have developed a strategy for avoiding implanting memories arising from one of the seven most common causes of implanted memories in psychodynamic therapy: 1) Satisfying own expectancies, 2) pleasing the therapist, 3) transferences and counter transferences, 4) as source of mental and emotional order, 5) as emotional defence, 6) as symbol and 7) from implanted philosophy. Freud taught us that child sexuality is “polymorphously perverted”, meaning that all kinds of sexuality is present at least potentially with the little child; and in dreams consciousness often go back to the earlier stages of development, potentially causing all kinds of sexual dreams and fantasies, which can come up in therapy and look like real memories. The therapist working with psychodynamic psychotherapy, clinical holistic medicine, psychiatry, and emotionally oriented bodywork, should be aware of the danger of implanting philosophy and memories. Implanted memories and implanted philosophy must be carefully handled and de-learned before ending the therapy. In conclusion “clinical holistic medicine” has developed a strategy for avoiding implanting memories.